1996
DOI: 10.1152/jn.1996.76.6.3633
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing in cerebral cortex of the marmoset monkey: effect of reversible SI inactivation on tactile responses in SII

Abstract: 1. Responsiveness within the hand region of the second somatosensory area of cortex (SII) was investigated in the marmoset monkey (Callithrix jacchus) in association with cooling-induced, reversible inactivation of the primary somatosensory area, SI. The aims were to determine whether thalamocortical systems in this primate species are organized according to a serial scheme in which tactile information is conveyed from the thalamus to SI and thence to SII as the next hierarchical level of processing and to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
93
3
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 0 publications
14
93
3
2
Order By: Relevance
“…Strong intrinsic connections between S1 and S2 are also compatible with the observation that transcranial magnetic stimulation over S1 can disrupt tactile discrimination in humans not only through a direct effect on the processing of tactile input in S1 but also through an indirect effect on the processing of tactile input in S2 (Cohen et al, 1991;Knecht et al, 2003;Hannula et al, 2008). Finally, it is important to mention that the observations suggesting that the responses elicited in S2 are relayed in S1 (Pons et al, 1992) are in contradiction with the findings of Zhang et al (1996), showing that in higher primates the responses to non-nociceptive somatosensory stimuli in S2 are mostly unaffected by the reversible inactivation of S1 by cooling, thus indicating that the bulk of the inputs triggering the responses in S2 are, in fact, not relayed through S1. Allison et al (1989a,b) used direct intracranial recordings performed in patients to observe that non-nociceptive somatosensory stimuli elicit responses of earlier latency in S1 compared with S2.…”
Section: Parallel Processing Of Non-nociceptive Input In S1 and S2supporting
confidence: 75%
See 1 more Smart Citation
“…Strong intrinsic connections between S1 and S2 are also compatible with the observation that transcranial magnetic stimulation over S1 can disrupt tactile discrimination in humans not only through a direct effect on the processing of tactile input in S1 but also through an indirect effect on the processing of tactile input in S2 (Cohen et al, 1991;Knecht et al, 2003;Hannula et al, 2008). Finally, it is important to mention that the observations suggesting that the responses elicited in S2 are relayed in S1 (Pons et al, 1992) are in contradiction with the findings of Zhang et al (1996), showing that in higher primates the responses to non-nociceptive somatosensory stimuli in S2 are mostly unaffected by the reversible inactivation of S1 by cooling, thus indicating that the bulk of the inputs triggering the responses in S2 are, in fact, not relayed through S1. Allison et al (1989a,b) used direct intracranial recordings performed in patients to observe that non-nociceptive somatosensory stimuli elicit responses of earlier latency in S1 compared with S2.…”
Section: Parallel Processing Of Non-nociceptive Input In S1 and S2supporting
confidence: 75%
“…This difference in hierarchical organization has been interpreted as the result of an evolutionary shift from a phylogenetically older parallel organization to a more recent serial organization of somatosensory processing in S1 and S2 (Mountcastle, 2005). However, a small number of studies have suggested the opposite: that, even in higher primates, non-nociceptive somatosensory input is processed in parallel in S1 and S2 Zhang et al, 1996Zhang et al, , 2001Karhu and Tesche, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption has been tested in a number of different species by anatomical and inactivation studies (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Cortical Touch Pathways -Does Processing Occur In Series?mentioning
confidence: 99%
“…However, there is also evidence that visual information is processed in parallel by multiple cortical areas (Herkenham 1980;Weyand and Swadlow 1986). A similar ambiguity characterizes somatosensory cortical regions, with evidence existing for both serial and parallel processing by different cortical areas (Burton 1991;Coleman et al 1999; Dykes 1983;Pons et al 1992;Turman et al 1995;Zhang et al 1996).…”
Section: Introductionmentioning
confidence: 98%
“…However, there is also evidence that visual information is processed in parallel by multiple cortical areas (Herkenham 1980;Weyand and Swadlow 1986). A similar ambiguity characterizes somatosensory cortical regions, with evidence existing for both serial and parallel processing by different cortical areas (Burton 1991;Coleman et al 1999; Dykes 1983;Pons et al 1992;Turman et al 1995;Zhang et al 1996).In rodents, stimulation of the mystacial vibrissae (whiskers) evokes responses both in the first somatosensory ("barrel") cortex (SI) and in the second somatosensory cortex (SII; so named because it was discovered later than SI; White 1987). However, apart from the fact that whisker-related neurons in SII have large receptive fields (Carvell and Simons 1986;Fabri and Burton 1991;Remple et al 2003), relatively little is known about the functional organization of this cortical area.…”
mentioning
confidence: 98%